Extraction and identification of Carnosines from Alkhshni Fish Liza abu L. by using different techniques - Ali, Rawdha Mahmood; AL-Mossawi, Aum-El-Bashar H. J.; Mohammed, Lena Samer (Iraqi Journal of Aquaculture, 2021)
Carnosines were extracted from alkhshni fish Liza abu L. by using alcohol and water separation,Carnosines were identificated in several ways including spectroscopy identification using UV-visible and Fourier Transform infrared spectrophotometer technology and High Performance Liquid Chromatography (HPLC), spectral diagnostics using Ultraviolet-visible (UV) carnosines single peak showed at 215 nm wavelength and at diagnosis High Performance Liquid Chromatography (HPLC) retention time stood for standard carnosines 2.532 and author carnosines separated from 2.614 minutes alcoholic carnosines and 2.625 minutes aqueous carnosines, after undetecting the detection of toxicity assay of carnosines prepared on human blood serum and there have been no changes in its shape and appearance.